AAV mediated gene therapy as local treatment modality directed against amyloid beta oligomers in the brain using a high affinity, high specificity antibody: Nonhuman: Preclinical immunotherapeutic studies. (7th December 2020) - Blits, Bas; Gouwenberg, Yvonne; Gebuis, Titia; van der Loo, Rolinka; van Kesteren, Ronald E.; Smit, August B.; Preusting, Hans; Scheefhals, Guus
Abstract: Background: Alzheimer's disease (AD) is characterized by formation of amyloid beta (AB) plaques in the brain. Intermediate aggregates such as oligomers are considered to be the most toxic. Using AAV gene therapy, we express an antibody specifically directed against these AB oligomers. Local expression in the brain avoids the challenge of inefficient blood brain barrier transfer, and AAV vector administration would be needed only once for a long‐lasting effect. In this project, we are designing and characterizing AAV‐5 based vectors for the development of a gene therapeutic immunotherapy for AD. Method: AAV‐5 vectors were chosen as safe and effective delivery system for antibody expression and secretion in the brain. To test whether the generated recombinant AAV is functional, primary hippocampal neurons were infected and analyzed for transgene expression. Oligomer‐binding functionality of the expressed antibody was analyzed using ELISA. Moreover, AAV vectors were administered in vivo, either directly into the hippocampus or intracerebroventricular of wild type mice. Result: Recombinant AAV‐5 particles were able to infect and transduce primary hippocampal neurons. Western blot analysis revealed presence of antibody both in cell homogenate and secreted in medium. Functionality of the antibody was demonstrated by binding AB oligomers in an ELISA. In vivo, both routes of administration resulted in transduction patterns that could well be used to target an AD diseased brain. Conclusion: Recombinant AAV‐5 vector encoding for the antibody is tested positive in vitro and in vivo, suggesting that the antibody can be expressed and secreted in the brain to target AB oligomers at the site where it is needed. Future studies should reveal whether native AB oligomers are also recognized and efficiently neutralized in an appropriate mouse model of AD resulting in enhanced cognitive performance.